Acidosis ruminal en bovinos lecheros: Implicaciones sobre la producción y la salud animal - Granja Salcedo, Yury Tatiana [UNESP]; Ribeiro Jr., Carlos Stefenson [UNESP]; Toro Gomez, Daniela Juliana; Rivera Calderón, Luis Gabriel; Machado, Mirela [UNESP]; Manrique Ardila, Adalberto (My University, 2012)
Ruminal acidosis is a major problem in the production of cattle fed diets rich in concentrates, especially in cows of high milk production. During rumen acidosis rumen pH is depressed due to the accumulation of volatile fatty acids and the decline of the mechanisms responsible for rumen buffering. Among the main causes of acidosis include consumption of diets high in fiber carbohydrates and lack of effective fiber added to them. The increase in ruminal acidity and osmolality by the accumulation of acids can alter the integrity of the rumen wall, decrease blood pH and cause fatal dehydration in cattle. Ruminal acidosis results in a decrease in food consumption, the reduction in the digestibility of fibrous foods, a possible depression of milk fat and sometimes diarrhea, laminitis, displaced abomasum, liver abscesses and chronic rumintis. Ruminal acidosis is classified as acute or subacute clinical or subclinical. This paper is a review of ruminal acidosis in cattle in high production systemically reviewing this disease and its implications for both health and animal production.
Ruminal acidosis in dairy cattle: Implications for animal health and production
Keywords: Acidosis; Cattle; Fat milk; Non-fibrous carbohydrates; Ruminal pH; VFA; Animalia; Bos